Fostering Islamic Personality Students through The Role of Islamic Religious Education Teachers - Usman, Muhammad Umair Khan; Madania, Intan; Ratna, Rizky Dwi; Nur Kholis, Mohammad Maulana (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to describe the role of Islamic education teachers in shaping students' Islamic personality character. What is the role of Islamic education teachers in collaborating with Islamic education methods? How do Islamic Education teachers foster students in everyday life? How do teachers develop learning strategies in the Industrial Revolution era? This article uses literature study research, which collects sources from books and scientific articles. The findings in this paper are that teachers, in developing children's character, must be consistent with the principles of the teaching profession. Teachers have a dual role as motivators, collaborators, mentors, role models, and educators. The role serves to improve not only students' intelligence but also Islamic values. This role of teacher is also called scientific integration, namely balancing science education with cultural and Islamic values.